STUDENTS' PERCEPTIONS ON THE USE OF GOOGLE CLASSROOM ON LISTENING COMPREHENSION SUBJECT AT ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU - Nurul Asyiqin; Jismulatif Jismulatif; Dahnilsyah Dahnilsyah (International Journal of Educational Best Practices, 2022)
The purpose of this study is to find out the students' perceptions on the use of Google Classroom on listening comprehension subjects during the course of the Covid-19 pandemic. In this study, the method was quantitative research and the instrument used was a questionnaire designed by Chyntia (2018) and Shaharanee et al. (2016). There were 20 items in the questionnaire. Eighty-five students from the English Study Program at Universitas Riau participated in this study. The data were analyzed using frequency and mean. The findings indicate that the students positively perceive the use of Google Classroom on listening comprehension subjects. The results show that the Google Classroom used in listening comprehension subjects was efficient because the application became an alternative way to conduct learning activities from home. The students agree that Google Classroom is an efficient, comfortable, and economical application for listening comprehension subjects.